1972
DOI: 10.1145/361268.361278
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of disk scheduling policies

Abstract: Five well-known scheduling policies for movable head disks are compared using the performance criteria of expected seek time (system oriented) and expected waiting time (individual I O request oriented). Both analytical and simulation results are obtained. The variance of waiting time is introduced as another meaningful measure of performance, showing possible discrimination against individual requests. Then the choice of a utility function to measure total performance including system oriented and individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A reordering buffer can be used to rearrange the incoming sequence of accesses in such a way that latencies are reduced. This problem is known as disk scheduling (see, e. g., [17]). …”
Section: Introductionmentioning
confidence: 99%
“…A reordering buffer can be used to rearrange the incoming sequence of accesses in such a way that latencies are reduced. This problem is known as disk scheduling (see, e. g., [17]). …”
Section: Introductionmentioning
confidence: 99%
“…The shortest seek time first (SSTF) scheduler is a greedy scheduler that first serves the requests on the nearest track to minimize seek time [4,5]. There are several drawbacks to using SSTF: i) it does not take into account the rotational delay, which may be (at least) equally important to the seek time in modern disk drives; ii) since the middle disk tracks are more likely to be chosen by the SSTF algorithm, the pending requests located close to the inner and outermost disk tracks may potentially starve, leading to unfairness among tracks; iii) the disk's internal details may not be available to the host OS, which may then only approximate SSTF, for example by a nearest block first (NBF) algorithm [1].…”
Section: Shortest Seek Time First Schedulermentioning
confidence: 99%
“…However, request 5 arrives just before the service completion of request 3, which occurs at time t 1 . The algorithm SCAT F v2B (2,2) is then run at time t 1 , with request 5 taken into account to find the shortest cumulative access time two-hop sequence, which turns out to be (5,1). Once the service of request 5 completes, request 6 has just arrived.…”
Section: Scatfv1a Scatfv1b Scatfv2a Scatfv2bmentioning
confidence: 99%
“…A number of logical sequences are possible, (15,16) e.g. SCAN, shortest-seek-time-first, but studies have shown that this processing method only produces an advantage at comparatively high rates of transactions.…”
Section: Processing Mode Of Master Filementioning
confidence: 99%